2021
DOI: 10.1111/jcpt.13366
|View full text |Cite
|
Sign up to set email alerts
|

Optimal trough concentration of teicoplanin for the treatment of methicillin‐resistant Staphylococcus aureus infection: A systematic review and meta‐analysis

Abstract: What is known and objective: It has been recommended that the trough concentration (C min ) of teicoplanin should be maintained at ≥20 μg/ml for difficult-to-treat complicated infections caused by methicillin-resistant Staphylococcus aureus (MRSA).Conversely, C min of teicoplanin of at least 10 μg/ml is required for non-complicated MRSA infections. Considering the low incidence of nephrotoxicity for teicoplanin, C min = 15-30 μg/ml has been suggested for most MRSA infections. Thus, we assessed the clinical eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…Our previous studies indicated that the trough concentration (C min ) of TEI is correlated with the clinical efficacy of TEI therapy ( Tang et al, 2020 ; Ren et al, 2021 ). It has been recommended that the C min of TEI (at least 10 μg/ml is required for non-complicated MRSA infections) should be maintained at 15–30 μg/ml for most of the methicillin-resistant Staphylococcus aureus (MRSA) infections ( Abdul-Aziz et al, 2020 ; Hanai et al, 2021 ). Our previous studies suggested that a high-loading and maintenance dosage regimen (6–12 mg/kg, q12 h × 3 doses and 6–12 mg/kg qd) is required to maintain the C min of TEI in its therapeutic range at the early stage of treatment, and no reduction in the loading dose is required for renal dysfunction patients ( Tang et al, 2020 ; Ren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies indicated that the trough concentration (C min ) of TEI is correlated with the clinical efficacy of TEI therapy ( Tang et al, 2020 ; Ren et al, 2021 ). It has been recommended that the C min of TEI (at least 10 μg/ml is required for non-complicated MRSA infections) should be maintained at 15–30 μg/ml for most of the methicillin-resistant Staphylococcus aureus (MRSA) infections ( Abdul-Aziz et al, 2020 ; Hanai et al, 2021 ). Our previous studies suggested that a high-loading and maintenance dosage regimen (6–12 mg/kg, q12 h × 3 doses and 6–12 mg/kg qd) is required to maintain the C min of TEI in its therapeutic range at the early stage of treatment, and no reduction in the loading dose is required for renal dysfunction patients ( Tang et al, 2020 ; Ren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hanai et al believed that the clinical efficacy was better when C min was 15–30 mg/L than when it was <15 mg/L, 29 and another study also found that the treatment failed when patients with ARC used standard dosages 2 . The presents study did not find a significant difference in the clinical effectiveness rate between the ARC and non‐ARC groups (77.3% vs. 62.5%, respectively; p = 0.227) or between the HD and LD groups (73.9% vs. 65.2%, respectively; p = 0.522).…”
Section: Discussionmentioning
confidence: 99%
“…C min was 15-30 mg/L than when it was <15 mg/L, 29 and another study also found that the treatment failed when patients with ARC used standard dosages. 15 Therefore, to determine whether the clinical efficacy could be further affected by teicoplanin exposure when ARC is present, a larger sample should be used to address the limitations associated with the small numbers of cases in these studies.…”
Section: Hanai Et Al Believed That the Clinical Efficacy Was Better Whenmentioning
confidence: 95%
“…Since it is difficult to obtain multiple serum teicoplanin concentrations to determine the AUC in the clinical setting, trough serum concentration monitoring is used as a surrogate marker for AUC to monitor the teicoplanin levels. 5 …”
Section: Introductionmentioning
confidence: 99%